Triangulocarpon patanii. A new genus of drupaceous fruit from the Deccan Intertrappean Beds of Marai Patan, Tahsil-Jivati, Dist.-Chandrapur, Maharashtra, India - Rupam H. Nimgade; Rajesh R. Dahegaonkar; Sanjay W. Patil (The Bioscan, 2025)
The present paper describes a new petrified fruit from the Deccan Intertrappean Beds of Marai Patan, Taluka Jiwati, Dist.-Chandrapur, Maharashtra, India. The fruit is triangular, unilocular, fibrous, dicotyledonous, and indehiscent with basal placentation. The pericarp is differentiated into epicarp, mesocarp and endocarp. The fruit measures about 750 μm in length and 868 μm in width. The pedicel is present and measures about 260.5 μm in length, while a single, oblanceolate stripy outgrowth, the Umbo, is present. The fruit shows a folded embryo with the triangular mass of endosperm. The fruit discussed in this paper is compared with the reported drupaceous fossil flora and the modern living genera from the families like Malvaceae, Sapindaceae, Boraginaceae, Trimeriaceae, Sterculiaceae, Tiliaceae and Convolvulaceae. None of the characters of this fruit shows affinity with that of any fossil or living flora, resulting in the formation of a new genus, Triangulocarpon patanii. The generic name signifies the shape of the present material, whereas the specific epithet is derived from the name of the locality the fossiliferous chert was collected from.